GERAKAN HIJAU: EDUKASI LINGKUNGAN DAN AKSI PENANAMAN DI KAWASAN HUTAN TERDEGRADASI BAGI ANAK-ANAK - Siahaya, Ludia; Parera, Lydia Riekie; Latupapua, Lesly; Maail, Rohny (Universitas Pattimura, 2025)
Green movement through environmental education at an early age can form a sustainable mindset and positive values, so that children will grow up with a high awareness to preserve nature. Activities based on direct experience, such as planting actions, increase children's understanding of the ecological function of trees and foster a sense of responsibility for the surrounding environment. The stages of implementing this activity include Preparation of interesting Materials, Preparation of Saplings, Preparation of Planting Locations, Initial Measurement of Children's Knowledge and Attitudes towards the Environment, Presentation of Materials accompanied by Evaluation of the Ability to Capture the Material presented, and Planting Actions. After the presentation of the material, the children experienced a change in understanding about who is responsible for protecting the environment and gave a positive response to the role and function of forests for life by asking questions and answering the questions given. In addition, children are motivated to carry out planting actions at the activity location and around their respective homes.